Intra- und Interrater-Reliabilität bei Ausdauertests der tiefen zervikalen Flexoren und zervikalen Extensoren bei Patienten mit und ohne subklinische Nackenschmerzen - Alahmari, Khalid A.; Reddy, Ravi S.; Silvian, Paul; Ahmad, Irshad; Kakarparthi, Venkata Nagaraj; Rengaramanujam, Kanagaraj (Physikalische Medizin, Rehabilitationsmedizin, Kurortmedizin, 2019)
Purpose Deep neck flexor (DNF) and neck extensor (NE) muscle endurance tests are a part of standard assessment procedure in routine physical therapy practice and these tests needs to be reliable.Materials and Methods Intra-rater (between-day) and inter-rater (within-day) reliability was assessed for 2 neck muscle endurance tests in 26 subclinical neck pain and 31 normal subjects by 2 blinded assessors. The tests conducted included 1) DNF endurance test performed in supine and 2) NE muscle endurance test performed in prone position.Results and discussion The Intra-rater and inter-rater reliability was determined by means of Intra Class Correlation (ICC), with 95% confidence intervals. The intra rater reliability testing showed good agreement for both DNF (ICC=0.76 and 0.78) and NE muscle endurance (ICC=0.75 and 0.76) tests. Meanwhile, the inter-rater reliability showed moderate to good agreement for both DNF (ICC – 0.58 and 0.61) and NE muscle endurance tests (ICC – 0.57 and 0.74) in subjects with subclinical neck pain. Subclinical neck pain subjects had a significantly lower endurance holding times compared to normal (p<0.001).Conclusion The intra and inter rater reliability ranged from moderate to good agreement. Neck flexor and extensor muscle endurance can be measured reliably in a clinical setup in subjects with subclinical neck pain.
Keywords: Neck Pain; Physical Endurance; Assessment tools; Reproducibility of Results